Heart rate variability in individual psychotherapy: associations with alliance and outcome - Blanck, Paul; Stoffel, Martin; Bents, Hinrich; Ditzen, Beate; Mander, Johannes (The journal of nervous and mental disease, 2019)
AbstractHeart rate variability (HRV) can be conceptualized as a marker of an individual's capability to adaptively respond to its environment and has been linked with mental health. Although conceptually and empirically linked to social behavior and thus relevant in the therapeutic setting, HRV is s